1999
DOI: 10.1046/j.1365-2036.1999.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

Mouse model of Helicobacter pylori infection: studies of gastric function and ulcer healing

Abstract: Conventional mice with gastric ulcers can be successfully infected by both toxigenic and nontoxigenic H. pylori strains, and this infection causes an immediate suppression of gastric secretion and markedly delays the healing of ulcers due to the fall in mucosal microcirculation in the ulcer region, cytokine release and an impairment in the gastrin-somatostatin link that appears to be independent of gastritis and more pronounced with infection of toxigenic than nontoxigenic strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 51 publications
7
44
1
1
Order By: Relevance
“…Because IL-4 was administered 7 days before inoculation, it is possible that the cytokine reduces the initial level of colonization, increases its rate of clearance or both. As previously reported for mouse models (33,34) and human subjects (35) infected with H. felis or H. pylori, gastric acid levels in infected SOM ϩ/ϩ mice were lower than in uninfected animals (Fig. 8, which is published as supporting information on the PNAS web site).…”
Section: Il-4 Prevents H Felis Colonization In Som ؉͞؉ and Som ؊͞؊ Msupporting
confidence: 51%
“…Because IL-4 was administered 7 days before inoculation, it is possible that the cytokine reduces the initial level of colonization, increases its rate of clearance or both. As previously reported for mouse models (33,34) and human subjects (35) infected with H. felis or H. pylori, gastric acid levels in infected SOM ϩ/ϩ mice were lower than in uninfected animals (Fig. 8, which is published as supporting information on the PNAS web site).…”
Section: Il-4 Prevents H Felis Colonization In Som ؉͞؉ and Som ؊͞؊ Msupporting
confidence: 51%
“…Chronic ulcer by acetic acid injection into the gastric subserosa area, differently from acute ulcers, penetrates the muscle layer of the glandular area and, occasionally, relapses after wound healing, and is highly similar to the human gastric ulcer in light of its pathological characteristics and healing process (Okabe and Pfeiffer, 1972). Previous results indicate that Wistar rats with pre-existing gastric ulcers, experimentally produced by acetic acid injection, developed active ulcers when exposed to H. pylori, similar to the results of Konturek et al (1999), which were obtained with a different species (Souza et al, 2009). In order to evaluate the in vivo anti-H. pylori activity and to verify the presence of this bacteria in the gastric mucosa of ulcerated infected rats, the urease test and histopathological analysis should be carried out and monitored by the degree of cicatrisation of the gastric lesion.…”
Section: Some Considerationssupporting
confidence: 70%
“…After ulcer induction, the animals should be kept in propylene cages, with daily access to commercial food restricted to the time periods of 9-10 a.m. and 5-6 p.m., allowing for adequate fasting for administration of H. pylori, and of extract at 50, 100 and 200mg/kg doses of preparations, as well as of the standard drugs (amoxicillin 50mg/kg + clarithromycin 25mg/kg + omeprazole 20mg/kg). According to the method described by Konturek et al (1999), with modifications, 24h after ulcer induction by acetic acid, the animals should be inoculated intragastrically with 1 mL of H. pylori ATCC 43504 (9x10 8 ) suspended in Mueller-Hinton broth, by using a cannula appropriate for orogastric gavage. For the animals in the control, Sham and acetic acidinduced ulcer groups without H. pylori infection, only Mueller-Hinton broth should be orally administered.…”
Section: Ulcer Induction and Colonization By H Pylorimentioning
confidence: 99%
“…The fact that antibiotics and acid pump inhibitors prevented delayed healing resulting from H. pylori have offered valuable insights into the mechanisms of ulcer healing. Konturek's group 68,69) reported that Cag A and Vac A positive H. pylori water extract could delay ulcer healing in mice and rats. They contend that the underlying mechanism involves reduction of gastric mucosal blood flow, over-expression of cytokines, such as IL-1b and TNFa, and disruption of the balance between serum gastrin/somatostatin.…”
Section: Cox-2 and Paf Inhibitors And Plateletsmentioning
confidence: 99%